Friction stir welding and processing : science and engineering - Mishra, Rajiv Sharan (Springer International Publishing, 2014)
This book lays out the fundamentals of friction stir welding and processing and builds toward practical perspectives. The authors describe the links between the thermo-mechanical aspects and the microstructural evolution, and use of these for the development of the friction stir process as a broader metallurgical tool for microstructural modification and manufacturing. The fundamentals behind the practical aspects of tool design, process parameter selection and weld related defects are discussed. Local microstructural refinement has enabled new concepts of superplastic forming and enhanced low temperature forming. The collection of friction stir based technologies is a versatile set of solid state manufacturing tools.